Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1002/dev.420080507
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and hormonal effects of attachment object separation in surrogate‐peer‐reared and mother‐reared infant rhesus monkeys

Abstract: Mother-reared and surrogate-peer-reared rhesus monkeys were separated from their respective attachment objects at 6 months of age and tested for the following 9 weeks to determine their home-cage behavior and their pituitary-adrenocortical responses to stress. Both groups displayed a strong immediate behavioral response to separation which was characterized by increased vocalization, increased locomotion, and decreased self-play. However, the surrogate-peer-reared infants showed a subsequent recovery in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 12 publications
4
43
0
Order By: Relevance
“…This is in agreement with the findings of Meyer et al [1975]. There are several possible explanations for this effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the findings of Meyer et al [1975]. There are several possible explanations for this effect.…”
Section: Discussionsupporting
confidence: 93%
“…When socially reared monkeys are compared, motherreared infants appear more reactive to stressors than animals reared in a nursery with social partners. For instance, Meyer et al [1975] found that 6-month-old animals reared with surrogates and limited peer access displayed lower cortisol responses to the capture and separation of an infant housed nearby than did monkeys housed as pairs individually with their mothers. In addition, Clarke [1993] reported that 1-to 6-month-old, peer-reared infants demonstrated lower basal ACTH, but not cortisol, levels than infants housed individually with mothers, as well as smaller ACTH and cortisol increments to a stressor.…”
Section: Introductionmentioning
confidence: 98%
“…In humans, individuals who developed psychiatric disorders related to early adversity usually had lived a normal social life before the occurrence of the diseases. The fact that in rodents the effects of MS on the HPA axis can be reversed by later experience (27,28) makes this an important issue. To answer this question, we performed a long-term study to identify whether the effects that MS imposed on rhesus infants can be reversed after living a long and normal social life following the separation.…”
Section: Xiaolimentioning
confidence: 99%
“…Rhesus and squirrel monkeys exposed to prolonged early-life maternal deprivation exhibit elevated basal levels of cortisol (7-9), enhanced glucocorticoid feedback sensitivity (10), and heightened cortisol reactivity to social stress in some studies (11,12), but lower basal cortisol and reduced cortisol reactivity in others (9,13,14). The effect of maternal deprivation on SNS development in nonhuman primates has been studied infrequently.…”
mentioning
confidence: 99%